2009
DOI: 10.1002/pssc.200881522
|View full text |Cite
|
Sign up to set email alerts
|

Optical Kerr signals of GaAs/AlAs multilayer cavities for a short pulse

Abstract: Optical Kerr signals of GaAs/AlAs multilayer cavities with various quality factor (Q) were measured by an optical pump and probe technique with ultrashort pulses. Although the light intensity is enhanced in the cavities by Q, light power is restricted by the narrower spectrum of the cavity mode than that of the input ultrashort pulse. The measured Kerr signals showed larger dependence on the quality factor than that expected by simple consideration for the field enhancement effect by cavities. It seems that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…The thickness of the barrier layer at the center was adjusted to make the total thickness of the cavity layer equal to λ/2. The simulated light intensity of the cavity mode is also shown in the figure [7]. The simulated light is distributed in the complete multi-layers, although the maximum intensity is located at the cavity layer in the center.…”
Section: Experiments 21 Multilayer Micro-cavitymentioning
confidence: 97%
See 1 more Smart Citation
“…The thickness of the barrier layer at the center was adjusted to make the total thickness of the cavity layer equal to λ/2. The simulated light intensity of the cavity mode is also shown in the figure [7]. The simulated light is distributed in the complete multi-layers, although the maximum intensity is located at the cavity layer in the center.…”
Section: Experiments 21 Multilayer Micro-cavitymentioning
confidence: 97%
“…We showed through a simulation that large optical Kerr signals were obtained due to enhanced optical intensity and enlarged nonlinear phase shifts in the multilayer cavity structure. We experimentally demonstrated for the cavities composed of a GaAs halfwavelength-cavity (λ/2-cavity) layer and 11~15 pairs of GaAs (λ/4)/AlAs (λ/4) distributed Bragg reflector (DBR) layers on both sides that the nonlinear optical signal intensity depended on the Q-values of the cavity [7]. We also experimentally demonstrated an ultrafast response of the optical Kerr signal of less than one picosecond [8], which was limited by the photon lifetime of the cavity.…”
mentioning
confidence: 99%
“…Especially, difference frequency generation (DFG) methods with high conversion efficiency enable us to develop compact terahertz emitters operating at roomtemperature. A half-wavelength (λ/2) cavity structure sandwiched between two GaAs/AlAs distributed Bragg reflector (DBR) multilayers is useful for nonlinear optical devices such as all-optical Kerr gate switches [1,2] because extremely strong light field is realized in the λ/2 cavity layer. Recently, we have proposed a GaAs/AlAs coupled multilayer cavity structure, where two λ/2 cavity layers are coupled by the intermediate DBR multilayer, grown on a high-index GaAs substrate.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated the strong optical Kerr signals of a GaAs/AlAs multilayer cavity structures by inserting a resonant InAs quantum dots (QDs) as the half-wavelength (λ/2) cavity layer [1,2]. Recently, the numerical simulation using self-consistent transfer matrix method showed that the optical Kerr signal intensity of the GaAs/AlAs multilayer cavity structure is remarkably enhanced in proportional to the Q 4 [3], where Q is a quality factor depending on the numbers of distributed Bragg reflector (DBR) layers. It is quite important to confirm this extremely enhanced Q dependent signal for the future applications of nonlinear optical switches based on the GaAs/AlAs multilayer cavity structures.…”
Section: Introductionmentioning
confidence: 99%